A Methodological Note for the Development of Integrated Aquaculture Production Models - Tsani, Stella; Koundouri, Phoebe (Frontiers in Marine Science, 2018)
Aquaculture production can yield significant economic, social and environmental effects. These exceed the financial costs and benefits aquaculture producers are faced with. We propose a methodology for the development of integrated production models that allow for the inclusion of the socio-economic and environmental effects of aquaculture into the production management. The methodology develops on a Social Cost-Benefit Analysis context and it includes three parts: i) environmental, that captures the interactions of aquaculture with the environment, ii) economic, that makes provision for the incorporation of economic determinants in the production models and iii) social, that introduces the social preferences to the production and management process. Alternatives to address data availability issues are also discussed. The methodology extends the assessment of the costs and benefits of aquaculture beyond pure financial metrics and beyond the quantification of private costs and benefits. It can also support the development of integrated models of aquaculture production that take into consideration both the private and the social costs and benefits associated with externalities and effects not appropriately captured by market mechanisms. The methodology can support aquaculture management and policies targeting sustainable and efficient aquaculture production and financing from an economic, financial, social and environmental point of view.